ketu mutant mice uncover an essential meiotic function for the ancient RNA helicase YTHDC2 - Jain, Devanshi; Puno, M Rhyan; Meydan, Cem; Lailler, Nathalie; Mason, Christopher E; Lima, Christopher D; Anderson, Kathryn V; Keeney, Scott (eLife, 2018)
Mechanisms regulating mammalian meiotic progression are poorly understood. Here we identify mouse YTHDC2 as a critical component. A screen yielded a sterile mutant, ‘ketu’, caused by a Ythdc2 missense mutation. Mutant germ cells enter meiosis but proceed prematurely to aberrant metaphase and apoptosis, and display defects in transitioning from spermatogonial to meiotic gene expression programs. ketu phenocopies mutants lacking MEIOC, a YTHDC2 partner. Consistent with roles in post-transcriptional regulation, YTHDC2 is cytoplasmic, has 3′→5′ RNA helicase activity in vitro, and has similarity within its YTH domain to an N6-methyladenosine recognition pocket. Orthologs are present throughout metazoans, but are diverged in nematodes and, more dramatically, Drosophilidae, where Bgcn is descended from a Ythdc2 gene duplication. We also uncover similarity between MEIOC and Bam, a Bgcn partner unique to schizophoran flies. We propose that regulation of gene expression by YTHDC2-MEIOC is an evolutionarily ancient strategy for controlling the germline transition into meiosis.
Keywords: meiosis; MEIOC; Bam; Bgcn; gametogenesis; m6A